2014
DOI: 10.1152/ajpcell.00325.2013
|View full text |Cite
|
Sign up to set email alerts
|

Large-conductance voltage- and Ca2+-activated K+ channel regulation by protein kinase C in guinea pig urinary bladder smooth muscle

Abstract: Large-conductance voltage- and Ca(2+)-activated K(+) (BK) channels are critical regulators of detrusor smooth muscle (DSM) excitability and contractility. PKC modulates the contraction of DSM and BK channel activity in non-DSM cells; however, the cellular mechanism regulating the PKC-BK channel interaction in DSM remains unknown. We provide a novel mechanistic insight into BK channel regulation by PKC in DSM. We used patch-clamp electrophysiology, live-cell Ca(2+) imaging, and functional studies of DSM contrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 49 publications
2
35
0
Order By: Relevance
“…In contrast, the latter depends mainly on Ca 2ϩ entry through L-type VDCCs and not Ca 2ϩ release via RyRs as pharmacological inhibition of L-type VDCCs substantially reduces the steady-state BK current (53). Thus, ryanodine has been largely used as a pharmacological tool to separate the TBKCs from the steady-state BK currents in UBSM cells (53,60,62,114,121,152).…”
Section: Ubsm Bk Channel Regulation By Ca 2ϩ Signalsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the latter depends mainly on Ca 2ϩ entry through L-type VDCCs and not Ca 2ϩ release via RyRs as pharmacological inhibition of L-type VDCCs substantially reduces the steady-state BK current (53). Thus, ryanodine has been largely used as a pharmacological tool to separate the TBKCs from the steady-state BK currents in UBSM cells (53,60,62,114,121,152).…”
Section: Ubsm Bk Channel Regulation By Ca 2ϩ Signalsmentioning
confidence: 99%
“…Although BK channel regulation by PKC has been known in other cell types for quite some time (128,141), it was not until very recently when it was shown that PKC can also regulate BK channels in UBSM (62,64). Specifically, in guinea pig UBSM cells, PKC inhibits BK channel activity indirectly via a Ca 2ϩ -dependent mechanism involving the attenuation of the Ca 2ϩ release through RyRs while increasing the global intracellular Ca 2ϩ necessary to activate UBSM contraction (62). Upon pharmacological activation, PKC could phosphorylate proteins in the SR such as RyRs and/or PLB (Fig.…”
Section: Ubsm Bk Channel Regulation By M Receptor and Pkcmentioning
confidence: 99%
See 1 more Smart Citation
“…63 Indeed, a number of studies have revealed that PKC-dependent signaling pathways may play a significant role in the regulation of functions in UBSMCs. 1,37,64,65 An interaction of PKC with BK channels has been investigated at the molecular and functional level. 64,66 A plausible explanation for this interaction is that stimulation of M 3 Rs leads to diacylglycerol production, which activates PKC (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…PKC may cause direct inhibition of the SR Ca 2C pumps and/or RyRs, thereby resulting in suppression of BK channels in UBSMCs. 64 However, the assumption of a direct PKC-BK channel interaction or an indirect mechanism involving the SR Ca 2C store needs to be tested directly. It has been shown that PKC can phosphorylate specific serine residues on the BK channel a and b subunits, and a failure of phosphorylation of either subunit leads to a loss of the channel function when the serine residues were substituted for alanine.…”
Section: Introductionmentioning
confidence: 99%